PD-L1 Expression Correlated with p53 Expression in Pediatric Glioblastoma Multiforme - Jakub Litak; Wiesława Grajkowska; Justyna Szumiło; Paweł Krukow; Ryszard Maciejewski; Jacek Roliński; Cezary Grochowski (Brain Sciences, 2021)
High-grade gliomas are infrequent in the pediatric population compared to adults, nevertheless, mortality and morbidity caused by malignant gliomas in this group of patients remain significant. PD-L1 and PD-1 Immune checkpoints (IC) molecules maintain immunological balance between activation and suppression. Eighteen patients with a histopathological diagnosis of pediatric glioblastoma multiforme (GBM, WHO IV) were studied. In total, PD-L1 expression was detected in 8 patients (44%). The molecular aspect of IC and immunotherapy targeted on PD-1/PD-L1 axis in pediatric population may be a promising adjuvant therapy in pediatric glioblastoma multiform treatment, however, this subject requires further investigation.